Effects of Rainfall Variability and Land Cover Type on Soil Organic Carbon Loss in a Hilly Red Soil Region of Southern China - Mengqi Chang; Shengsheng Xiao; Yunhua Liao; Junjie Huang; Haifeng Li (Agronomy)
Rainfall intensity (RI) and land cover type are two important factors that affect soil erosion and thus the transfer and loss of soil organic carbon (SOC). However, the in situ quantitative monitoring of SOC loss under natural rainfall and various land cover types restored on eroded lands has not been thoroughly examined. In order to further study the effects of rainfall changes and vegetation types on SOC loss in the red soil region of Southern China, the Jiangxi Eco-Science Park of Soil and Water Conservation in De’an County, Jiangxi Province, was taken as the research object. Considering natural rainfall and based on the long-term field in situ monitoring of rainfall and runoff and sediment data, we studied the effects of three land cover types (bare land, orchards, and grass cover) on surface runoff, sediment production, and SOC loss in relation to 1 hour of RI during natural rainfall in the red soil region of Southern China during rainy seasons of 2020 and 2021 (March to August). Compared with bare land plots, the orchard and grass cover plots had surface runoff reductions of 67% and 98%, respectively, and sediment reductions of 79% and 99% over the two rainy seasons, respectively. With an increasing RI over 1 hour, total SOC loss increased for each of the three land cover types. More SOC loss was associated with sediments, and the enrichment ratio of SOC in the sediments (ERoc) decreased significantly. The ERoc values decreased in the following order: bare land (1.23) > orchard (1.08) > grass cover (0.81). Bare land exhibited the highest proportion of SOC associated with sediment in the total SOC loss (Ps), at 68.69%, followed by the orchard plots, at 55.02%, and then the grass cover plots at 49.24%. With the transfer of land cover type from bare land to orchard and to grass cover (decreased soil loss intensity, SLI), more SOC was lost associated with runoff in the form of dissolved organic carbon (DOC); the values of ERoc and organic carbon loss intensity (CLI) also decreased significantly. These findings are crucial to improving our understanding of the regulatory mechanisms of rainfall changes and land cover types on SOC loss during soil erosion.